Plasmodium falciparum infection in febrile Congolese children: prevalence of clinical malaria 10 years after introduction of artemisinin‐combination therapies. Issue 12 (18th October 2016) - Etoka‐Beka, Mandingha Kosso; Ntoumi, Francine; Kombo, Michael; Deibert, Julia; Poulain, Pierre; Vouvoungui, Christevy; Kobawila, Simon Charles; Koukouikila‐Koussounda, Felix
Abstract: Objectives: To investigate the proportion of malaria infection in febrile children consulting a paediatric hospital in Brazzaville, to determine the prevalence of submicroscopic malaria infection, to characterise Plasmodium falciparum infection and compare the prevalence of uncomplicated P. falciparum malaria according to haemoglobin profiles. Methods: Blood samples were collected from children aged <10 years with an axillary temperature ≥37.5 °C consulting the paediatric ward of Marien Ngouabi Hospital in Brazzaville. Parasite density was determined and all samples were screened for P. falciparum by nested polymerase chain reaction (PCR) using the P. falciparum msp‐2 marker to detect submicroscopic infections and characterise P. falciparum infection. Sickle cell trait was screened by PCR. Results: A total of 229 children with fever were recruited, of whom 10% were diagnosed with uncomplicated malaria and 21% with submicroscopic infection. The mean parasite density in children with uncomplicated malaria was 42 824 parasites/μl of blood. The multiplicity of infection (MOI) was 1.59 in children with uncomplicated malaria and 1.69 in children with submicroscopic infection. The mean haemoglobin level was 10.1 ± 1.7 for children with uncomplicated malaria and 12.0 ± 8.6 for children with submicroscopic infection. About 13% of the children harboured the sickle cell trait (HbAS); the rest had normal haemoglobin (HbAA). No difference in prevalence of uncomplicated malaria and submicroscopic infection, parasite density, haemoglobin level, MOI and P. falciparum genetic diversity was observed according to haemoglobin type. Conclusion: The low prevalence of uncomplicated malaria in febrile Congolese children indicates the necessity to investigate carefully other causes of fever.